Development of 3D Printed Multi-Layered Orodispersible Films with Porous Structure Applicable as a Substrate for Inkjet Printing - Elbl, Jan; Veselý, Martin; Blaháčková, Dagmar; Ondruš, Jaroslav; Kulich, Pavel; Mašková, Eliška; Mašek, Josef; Gajdziok, Jan (Pharmaceutics, 2023)
The direct tailoring of the size, composition, or number of layers belongs to the advantages of 3D printing employment in producing orodispersible films (ODFs) compared to the frequently utilized solvent casting method. This study aimed to produce porous ODFs as a substrate for medicated ink deposited by a 2D printer. The innovative semi-solid extrusion 3D printing method was employed to produce multilayered ODFs, where the bottom layer assures the mechanical properties. In contrast, the top layer provides a porous structure for ink entrapment. Hydroxypropyl methylcellulose and polyvinyl alcohol were utilized as film-forming polymers, glycerol as a plasticizer, and sodium starch glycolate as a disintegrant in the bottom matrix. Several porogen agents (Aeroperl® 300, Fujisil®, Syloid® 244 FP, Syloid® XDP 3050, Neusilin® S2, Neusilin® US2, and Neusilin® UFL2) acted as porosity enhancers in the two types of top layer. ODFs with satisfactory disintegration time were prepared. The correlation between the porogen content and the mechanical properties was proved. A porous ODF structure was detected in most samples and linked to the porogen content. SSE 3D printing represents a promising preparation method for the production of porous ODFs as substrates for subsequent drug deposition by 2D printing, avoiding the difficulties arising in casting or printing medicated ODFs directly.